2016
DOI: 10.3346/jkms.2016.31.9.1351
|View full text |Cite
|
Sign up to set email alerts
|

Statement on Publication Ethics for Editors and Publishers

Abstract: The digitization and related developments in journal editing and publishing necessitate increasing the awareness of all stakeholders of science communication in the emerging global problems and possible solutions. Journal editors and publishers are frequently encountered with the fast-growing problems of authorship, conflicts of interest, peer review, research misconduct, unethical citations, and inappropriate journal impact metrics. While the number of erroneous and unethical research papers and wasteful, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 27 publications
1
18
0
1
Order By: Relevance
“…As the main conclusions of the articles inserted in this review, we have scientific productivism (19)(20) , the evaluation systems in relation to the productions by researchers/journals (19,(21)(22)(23)(24) , adequate/inadequate practices for publication (10,(20)(21)(22)(23)25) , the IF (22,25) used to classify periodicals, and the internationalization of national journals (19) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the main conclusions of the articles inserted in this review, we have scientific productivism (19)(20) , the evaluation systems in relation to the productions by researchers/journals (19,(21)(22)(23)(24) , adequate/inadequate practices for publication (10,(20)(21)(22)(23)25) , the IF (22,25) used to classify periodicals, and the internationalization of national journals (19) .…”
Section: Discussionmentioning
confidence: 99%
“…The evaluated articles have presented evidence levels classified as 5 (10,19,21,(23)(24)(25) and 4 (20,22) , which demonstrated that this matter has been discussed by authors with the intent of reflecting on these themes, exposing their opinions. On the other hand, two articles have used the descriptive method to discuss ethic scores in research and the editors' work.…”
Section: Specialist Opinion Level Of Evidence:mentioning
confidence: 99%
“…These journals are dangerous as they infect the medical academia with unnecessary and potentially uncorrected publications. Gasparyan et al (2016b) suggest that one significant threat of these predatory journals is the large amount of wasteful and redundant published data that would have been rejected by more highly regarded/ established journals. It has also been suggested that some predatory publications do not follow the strict guidelines against plagiarism that preserve the integrity of medical research (Jansen and Forget, 2012).…”
Section: Predatory Publishingmentioning
confidence: 99%
“…Additionally, a group of software specialists, researchers and publishers developed a digital platform to match English manuscript titles and abstracts with relevant and trusted journals (https://www.journalguide.com/). Finally, experts from various professional backgrounds have publicized statements on the ‘pollution’ of the scientific evidence accumulation (2829) and proposed criteria of best target journals, which may sideline outlets with unethical publishing models (3031). …”
Section: Tackling the Issue Of Predatory Publishingmentioning
confidence: 99%